Rise of terrorism and secessionism in Eurasia / edited by V.D. Chopra - "Chopra,V. D. (ed.)" (New Delhi, 2001)
This book examines on the basis of empirical studies, the rise if terrorism,secessionism and ethenic conflicts in the beginning of the 21st century in the entire belt of Eurasia. If you peel off this hard surface,and do strip mining, You come come across various layers beneath the surface. These layers include the imperialist policy of 'divide and rule' in the colonial period; accentuation of conflictsby the vested interests of the cold war period; moral and material support including supply of massive military hardware by certain foreign powers and above all the new nexus which has developed between terrorists,drug mafia, illicit arms dealers and criminals. About The Author:- V.D. Chopra, is a noted expert on external affairs and nuclear policy, and a peace Activist. Contents:- Message from the President of India Message from the Prime Minister of India Preface List of Contributors Introduction Terrorism and the Erosion of State Power The United States and International Terrorism in South Asia Towards a Political Economy of Intra State Conflicts Latest Trends in Terrorism Rise of Terrorism and Secessionism in the 21st Century Conflicting Perceptions Rise of Terrorism and Secessionism in South Asia-A Bahai Viewpoint Terrorism and National Security Concerns Pakistan and Afghanistan as Sources of Terrorism in the Region Transformation of Pakistan and Afghanistan as Springboards of Cross Country Terrorism in the Region The face of the Proxy War in J & K Islamist Extremism and Terrorism in Kashmir Militancy in Jammu and Kashmir: A Study of Actors, Objectives and Strategies 'Cross-Border' Terrorism in Punjab Islamic Factor and Fundamentalist Threat in Central Asia Rise of Islamic Extremism in West Asia and North Africa Pakistan and Taliban Role in Chechnya Conflict Chechnya: Background and Prospects The Yogaslav Tragedy Nature and Genesis of Terrorism and Ethnic Conflicts in Indonesia Ethnic Issues and Insurgency in Xinjian
Keywords: Tterrorism-Eurasia